The emergence of Bangladesh interdisciplinary perspectives - Khondker, Habibul Haque; Muurlink, Olav; Bin Ali, Asif (Palgrave Macmillan, 2022)
This book analyses and celebrates the first 50 years of Bangladesh as a nation, bringing insights from key scholars in Bangladeshi studies to an international audience, as well as bringing home to a domestic audience the work of some of the nations greatest intellectual exports, the Bangladeshi scholars who have made a mark in their field of study in academia. Habibul Haque Khondker is Professor of Sociology at Zayed University, Abu Dhabi. He is the co-editor of Covid-19 and Governance (2021). Olav Muurlink is Head of Country, Bangladesh, and chair of the NGO Cooperation in Development (Australia) Incorporated. He is Associate Professor in Sustainable Innovation at Central Queensland University. Asif Bin Ali a journalist turned academic, is Erasmus Mundus Fellow (2019-2021) at Swansea University, the UK, and Aarhus University, Denmark. He is the lead editor of Buddhist Nationalism Rohingya Crisis and Contemporary Politics (2019).